2010
DOI: 10.3113/fai.2010.0296
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Ankle Brace Use in High School Volleyball Players: A Prospective Study

Abstract: This information may be helpful in deciding whether to recommend prophylactic ankle braces in volleyball players.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 33 publications
(32 reference statements)
0
36
0
Order By: Relevance
“…[2][3][4] While these findings may be the result of methodological differences across studies, such as study design or type of ankle brace used as the intervention, it may be due to the different demands of each sport on the athlete. Based on the nature of football and basketball, athletes have more frequent opportunities for direct physical contact with other players in comparison with volleyball athletes.…”
Section: Implications For Practice Education and Future Researchmentioning
confidence: 78%
See 2 more Smart Citations
“…[2][3][4] While these findings may be the result of methodological differences across studies, such as study design or type of ankle brace used as the intervention, it may be due to the different demands of each sport on the athlete. Based on the nature of football and basketball, athletes have more frequent opportunities for direct physical contact with other players in comparison with volleyball athletes.…”
Section: Implications For Practice Education and Future Researchmentioning
confidence: 78%
“…2,3 It is also important to note that none of the 3 studies demonstrated an increased incidence of acute ankle sprains in the ankle-brace group compared with the control group. [2][3][4] Cumulatively, these findings indicate that the use of prophylactic ankle braces across an athletic season is effective in reducing acute ankle injuries in adolescent athletes.…”
Section: Implications For Practice Education and Future Researchmentioning
confidence: 92%
See 1 more Smart Citation
“…Several interventions have demonstrated success in achieving these goals without significant effects on quality of life or impeding athletic performance. By increasing passive restraints to ankle inversion and enhancing postural stability, prophylactic bracing in high-risk athletes has demonstrated success reducing the risk of primary and recurrent ankle sprain by up to 50% [41,106,107] . In one prospective randomized trial, Sitler et al [41] demonstrated a threefold increased risk for ankle sprain among unbraced basketball players when compared to braced athletes over a two-year time period at the United States Military Academy.…”
Section: Preventative Measuresmentioning
confidence: 99%
“…[9][10][11] Because of the relatively high prevalence and risk of ankle sprain, ankle braces are widely used and have been recognized as an effective prophylactic intervention to reduce the incidence, severity, and recurrence of ankle sprains. 4,[12][13][14][15][16][17][18][19][20][21] There are many different types of ankle braces available commercially, and most can be classified into categories of rigid, semi-rigid, or lace-up based upon their general design. A recent study by Denton et al regarding clinicians' (ie, physical therapists and athletic trainers) recommendations and perceptions associated with ankle brace use reported that lace-up braces were the type of ankle brace that were most frequently recommended prophylactically to prevent ankle sprain injuries.…”
Section: Introductionmentioning
confidence: 99%